2019
DOI: 10.1002/sctm.19-0242
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes impacts fetal precursor cell responses with potential consequences for offspring

Abstract: Fetal programming has been proposed as a key mechanism underlying the association between intrauterine exposure to maternal diabetes and negative health outcomes in offspring. To determine whether gestational diabetes mellitus (GDM) might leave an imprint in fetal precursors of the amniotic membrane and whether it might be related to adverse outcomes in offspring, a prospective case‐control study was conducted, in which amniotic mesenchymal stem cells (AMSCs) and resident macrophages were isolated from pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This situation obviously limited our ability to investigate differences in metabolic parameters between the groups. Another limitation of our study is the relatively small sample size; however, it is substantially larger than other studies analyzing the plasticity of placental-derived mesenchymal stromal cells [ 9 , 13 , 14 , 25 ]. Finally, we cannot discard the possibility that the stemness and angiogenic abilities of the hAMSCs were affected by cryopreservation and serial passaging [58], but as the same protocol was applied to GDM- and NGT-derived hAMSCs it should not affect our results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This situation obviously limited our ability to investigate differences in metabolic parameters between the groups. Another limitation of our study is the relatively small sample size; however, it is substantially larger than other studies analyzing the plasticity of placental-derived mesenchymal stromal cells [ 9 , 13 , 14 , 25 ]. Finally, we cannot discard the possibility that the stemness and angiogenic abilities of the hAMSCs were affected by cryopreservation and serial passaging [58], but as the same protocol was applied to GDM- and NGT-derived hAMSCs it should not affect our results.…”
Section: Discussionmentioning
confidence: 98%
“…Surface markers of the mesenchymal lineage were determined and analyzed by flow cytometry (FACS Aria III; BD Biosciences, San Jose, CA) meeting the minimum criteria defined by the International Society of Cell Therapy [ 28 ]. Briefly, hAMSCs (1 × 10 5 ) were incubated with a panel of primary antibodies (BD Pharmingen, San Diego, CA) as described [ 14 ]. Data analysis was performed using FACSDiva software (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications on the topic reported that maternal over-nutrition during pregnancy has repercussions on the child health the medium and long term, since metabolic changes that occur during fetal development can generate epigenetic changes, which will play an important role in the prevalence of transmitted obesity across generations. The conclusions of these articles reinforced the importance of weight control, both before and during pregnancy, and consumption of healthy foods in this period can reduce the risks of fetal programming of metabolic diseases [22][23][24].…”
Section: Discussionmentioning
confidence: 85%
“…However, the underlying mechanism is poorly understood. The most promising hypothesis is that suboptimal intrauterine environments during pregnancy with PE may permanently alter the organ structure and biological feedback mechanism of the fetus, increasing the individual’s susceptibility to disease [ 42 , 43 ], and that stem cells may be involved in the influence of the in utero environment on the subsequent risk of disease onset in adult life [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%